Okay so how do we use augmented matrices and row

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 2 y - 2 z = -10 same uuuuu r x - 2 y + 3z = 7 4x + 2 y + 2z = 8 -3 x + 2 y - 2 z = -10 Now, with this new system we will replace the second equation with the sum of the first and second equations and we will replace the third equation with the sum of the first and third equations. Here is the resulting system of equations. x - 2 y + 3z = 7 5x + 5 z = 15 -2 x + z = -3 So, we’ve eliminated one of the variables from two of the equations. We now need to eliminate either x or z from either the second or third equations. Again, we will use elimination to do this. In this case we will multiply the third equation by -5 since this will allow us to eliminate z from this equation by adding the second onto is. © 2007 Paul Dawkins 324 http://tutorial.math.lamar.edu/terms.aspx College Algebra x - 2 y + 3z = 7 5x + 5 z = 15 -2 x + z = -3 same uuuuu r same uuuuu r ´ -5 uuuuu r x - 2 y + 3z = 7 5x + 5 z = 15 10 x - 5 z = 15 Now, replace the third equation with the sum of the second and third equation. x - 2 y + 3z = 7 5x + 5 z = 15 15 x = 30 Now, at this point notice that the third...
View Full Document

This note was uploaded on 06/06/2012 for the course ICT 4 taught by Professor Mrvinh during the Spring '12 term at Hanoi University of Technology.

Ask a homework question - tutors are online